2011
DOI: 10.1261/rna.2348111
|View full text |Cite
|
Sign up to set email alerts
|

Increased siRNA duplex stability correlates with reduced off-target and elevated on-target effects

Abstract: Argonaute (Ago) proteins form the core of RNA-induced silencing complexes (RISCs) and mediate small RNA-guided gene silencing. In RNAi, short interfering RNAs (siRNAs) guide RISCs to complementary target RNAs, leading to cleavage by the endonuclease Ago2. Noncatalytic Ago proteins, however, contribute to RNAi as well but cannot cleave target RNA and often generate off-target effects. Here we show that synthetic siRNA duplexes interact with all Ago proteins, but a functional RISC rapidly assembles only around A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 45 publications
2
63
0
Order By: Relevance
“…5A). Of note, the amount of pulled down Ago proteins resembles the protein expression levels (29,30). For further affinity measurements, we tested possible protein aggregation using dynamic light scattering (DLS) (Materials and Methods and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A). Of note, the amount of pulled down Ago proteins resembles the protein expression levels (29,30). For further affinity measurements, we tested possible protein aggregation using dynamic light scattering (DLS) (Materials and Methods and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Annotation of Argonaute-related literature yielded a number of reposts describing covalent modifications of AGO proteins implicated in post-translational regulations, namely phosphorylation (Zeng et al, 2008;Rudel et al, 2011;Horman et al, 2013;Mazumder et al, 2013;Shen et al, 2013;Lopez-Orozco et al, 2015;Patranabis andBhattacharyya, 2016), prolyl 4-hydroxylation (Qi et al, 2008;Wu et al, 2011), sumoylation (Josa-Prado et al, 2015, ubiquitination (Rybak et al, 2009; The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure.…”
Section: Post-translational Modifications Of Ago Proteinsmentioning
confidence: 99%
“…Phosphorylation has been detected on AGO1 and AGO2 in the PAZ domain (pS253, pT303, pT307), the PIWI domain (pS798), in the L2 linker region (pS387, pY393) and in the MID domain (pY529) (Rudel et al, 2011).…”
Section: Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…2 D and E). Relative Ago protein levels have only been estimated before (21,22). Such earlier quantifications relied on antibodies with different affinities and thus might not be accurate.…”
Section: Specific Isolation and Characterization Of Ago Protein Complmentioning
confidence: 99%